Role of fibronectin in the adhesion of Acinetobacter baumannii to host cells. - Younes Smani (Public Library of Science (PLoS), 2012)
Adhesion to host cells is an initial and important step in Acinetobacter baumannii pathogenesis. However, there is relatively little information on the mechanisms by which A. baumannii binds to and interacts with host cells. Adherence to extracellular matrix proteins, such as fibronectin, affords pathogens with a mechanism to invade epithelial cells. Here, we found that A. baumannii adheres more avidly to immobilized fibronectin than to control protein. Free fibronectin used as a competitor resulted in dose-dependent decreased binding of A. baumannii to fibronectin. Three outer membrane preparations (OMPs) were identified as fibronectin binding proteins (FBPs): OMPA, TonB-dependent copper receptor, and 34 kDa OMP. Moreover, we demonstrated that fibronectin inhibition and neutralization by specific antibody prevented significantly the adhesion of A. baumannii to human lung epithelial cells (A549 cells). Similarly, A. baumannii OMPA neutralization by specific antibody decreased significantly the adhesion of A. baumannii to A549 cells. These data indicate that FBPs are key adhesins that mediate binding of A. baumannii to human lung epithelial cells through interaction with fibronectin on the surface of these host cells.